Cultivo integrado da microalga Nannochloropsis oceânica em meio de cultivo alternativo de baixo custo econômico e do camarão marinho Litopenaeus vannamei em tanques berçários - Oliveira, Nathaniel Gomes de (2022)
Shrimp farming is a very important activity in Brazil and in the world. The use of pre-nursery and nursery and the use of integrated cultivation systems have been techniqu es used to enable a greater stocking density of cultivated shrimp and a better economic performance of shrimp farms companies. The use of microalgae to control water quality parameters in intensive aquaculture systems has been widely used, a technique known as “green water”. However, the cultivation of microalgae for the most diverse applications faces an economic obstacle due to the high costs of implementation and operation of medium and large-scale cultures. The use of cheaper culture media and mixo or heterotrophic microalgae growth has been studied by several authors. The objective of this work is to evaluate the development of the microalgae Nannochloropsis oceanica cultivated in an alternative medium of low economic cost, made by agricultural fertilizers, in experimental nursery ponds for marine shrimp Litopenaeus vannamei and to determinate the zootechnical performance of shrimp cultivated in the described conditions. The shrimp were cultivated for 28 days. Physical and chemicals parameters of the water, the cell density of the N. oceanica through the study and the zootechnical performance of the animals were evaluated. The experimental treatments were a total of five, being carried out in nursery tanks: a control without fertilization and algal inoculation (CTL), a treatment with f/2 medium, a more complex and complete culture medium in the supply of compounds for the cultivation of microalgae (T1), one with fertilization by alternative medium (Fertilizante3) without inclusion of an organic carbon source (T2), one with alternative medium and inclusion of refined sugar (T3) and one with alternative medium and inclusion of sugarcane molasses (T4). Treatment T2 had the highest productivity per volume and the highest average cell density of N. oceanica throughout the experiment with a lower concentration of ammonia in the water at the end of the experimental period. The concentration of nitrite and nitrate increases along the culture in the treatments, showing that the phytoplankton cell density was not capable of mitigate the presence of these compounds. The integrated cultivation of the microalgae N. oceanica and L. vannamei using and alternative medium composed of agricultural fertilizers showed low cell growth under the conditions tested and, consequently, a low regulatory role of the microalgae in the control of nitrogen compounds, not being positive for the improvement of shrimp zootechnical performance.